RheumaTool, a novel clinical decision support system for the diagnosis of rheumatic diseases, and its first validation in a retrospective chart analysis - Hannes Alder; Christian Marx; Johann Steurer; Maria M. Wertli; Pius Korner-Nievergelt; Giorgio Tamborrini; Thomas Langenegger; Andrina Eichholzer; Michael Andor; Andreas Krebs; Beat A. Michel; Lukas Wildi (Swiss Medical Weekly, 2020)
AIMS